Penentuan Kadar Ammonia (NH3) pada Limbah Cair K-36 dalam Rangka Pengendalian Pencemaran Lingkungan - Patri, Moh. Yogi (ALKIMIA, 2018)
This research aims to know the levels of ammonia (NH3) in the liquid waste K-36 PT. PUSRI Palembang. PT. PUSRI Palembang was one of five plant fertilizer Indonesia Holding that manages natural gas in such a way that it becomes ammonia and through further processes produce urea fertilizer granules. The process of making urea fertilizer very complex by using high technology. PT PUSRI Palembang is one of the STATE-OWNED company that manufactures and markets products in the form of urea fertilizer. As for the methods used for the determination of the levels of ammonia (NH3) in the liquid waste K-36, i.e. using Nessler method before it is analyzed using spectrophotometer UV-Vis instruments. the test results obtained on the acidity and the ammonia levels different – different, the level of acidity that can range in 8.2 to 9.3. Whereas the levels of ammonia in can range up to 130 ppm 240 ppm. the levels of ammonia in the water channel K-36 still belongs to secure because it is still in the range 200 ppm and will still be in the aeration to evaporate ammonia before water dumped into the river.